Hosting the comfortably exotic: Cosmopolitan aspirations in the sharing economy. Issue 2 (March 2018) - Ladegaard, Isak
This article draws on interviews with 43 Airbnb hosts in Greater Boston to analyze how this novel economic arrangement brings people together across difference. The first central finding is that a majority of the participants express a keen interest in engaging with the Other, by hosting guests of foreign nationalities and cultures, but they also filter for familiar characteristics. This paradox is conceptualized as a preference for the 'comfortably exotic' – hosts want difference, but not too much of it. The second central finding is that guest–host interactions generate cosmopolitan capital, i.e., particular forms of social and cultural capital, which suggests that exclusion from the home-sharing economy has opportunity costs on not just economic dimensions, but also on cultural and social dimensions.